Experiencias de estudiantes de pedagogía en la Facultad de Estudios Superiores Aragón en México: Contenidos curriculares y prácticas fuera del aula desde relatos e historietas - Álvarez Hernández, Gabriel Alejandro (Universidad de Costa Rica, 2019)
The students of the degree in pedagogy of the Aragón School of Higher Studies in Mexico are faced with the difficulty of not making sense of the theoretical contents that are part of the curriculum, fall into crisis and doubt about continuing to study or not this career. This work exposes some experiences of students who managed to overcome this situation from living the pedagogy outside of school. Methodologically, the work was interpretive with a qualitative approach, starting with hermeneutical phenomenology and dealing with the narrative biographical method. Likewise, the questionnaire and the conversational interview were used as instruments, as well as the story in the case of a single student. Initially we worked with 101 students, who were little more than 60% of the morning shift generation. Subsequently, with six for the interviews and consequently five categories of analysis were built, of which one stands out entitled The student and the "outside " The results showed that the student manages to give meaning and meaning to the curricular contents that the teachers teach them when they can articulate them with the concrete experience of the pedagogical task, either in a school or in any other work space where the pedagogy intervenes. Finally, it is concluded that there is a need for students to find meaning in what they are taught in specific practices outside the school in their professional activities.